Two-dimensiional elastic contact model for rubber covered rollers - Austrell P E; Olsson A K (Plastics,Rubber and Composites, 2013)
A model for the contact between a rubber covered roller and a rigid roller was developed using analytical functions.The model,being two-dimensional,connects the line load,geometric properties(roller radii,rubber thickness)and the shear modulus of the rubber to nip properties in the roller contact.The output from the model is the indentation of the rigid roller into thr rubber,the nip maximum pressure,the nip width and the surface strain in the centre of the nip.Moreover,the shape of the pressure distribution is also given as an analytical expression.The basic assumption relies on the work of Parish(-58and-61),but a developement of this work was performed,showing the influence of the rubber shear modulus and also how the surface strain in the nip can be described.The functional relatiionships are based on least squares fitting of analytical functions,depending on two master variables,to a large number of infinite element analysis results.
Keywords: Analytical expressions; Contact; Fit to FE-results; Nip properties; pressure profile; rubber covered rollers